Liver transplantation for metastatic neuroendocrine tumors. - Lang, H (1997)
OBJECTIVE: This article describes the experience with liver transplantation in patients with irresectable neuroendocrine hepatic metastases. SUMMARY BACKGROUND DATA: Liver transplantation has become an established therapy in primary liver cancer. On contrast, there is little experience with liver transplantation in secondary hepatic tumors. So far, in the majority of patients being transplanted for irresectable liver metastases, long-term results have been disappointing because of early tumor recurrence. Because of their biologically less aggressive nature, the metastases of neuroendocrine tumors could represent a justified indication for liver grafting. METHODS: In a retrospective study, the data of 12 patients who underwent liver transplantation for irresectable neuroendocrine hepatic metastases were analyzed regarding survival, tumor recurrence, and symptomatic relief. RESULTS: Nine of 12 patients currently are alive with a median survival of 55 months (range, 11.0 days to 103.5 months). The operative mortality was 1 of 12, 2 patients died because of septic complications or tumor recurrences or both 6.5 months and 68.0 months after transplantation. all patients had good symptomatic relief after hepatectomy and transplantation. Four of the nine patients who are alive have no evidence of tumor with a follow-up of 2.0, 57.0, 58.0, and 103.5 months after transplantation. CONCLUSIONS: In selected patients, liver transplantation for irresectable neuroendocrine hepatic metastases may provide not only long-term palliation but even cure. Regarding the shortage of donor organs, liver grafting for neuroendocrine metastases should be considered solely in patients without evidence of extrahepatic tumor manifestation and in whom all other treatment methods are no longer effective.